Uncertainty in the timing of diversification of flowering plants rests with equivocal interpretation of their fossil record - James W. Clark; Philip C. J. Donoghue (Royal Society Open Science)
The timing of the origin of crown-angiosperms exemplifies the impact of competing approaches to establishing evolutionary timescales. Fossils of unequivocal crown-angiosperms are not known from before the Cretaceous, and yet molecular estimates range from the Late Jurassic to the Permian. We show that the disagreement between molecular and palaeobotanical estimates is an artefact of interpretations of the fossil record. We employ relaxed molecular clock methods that reflect competing interpretations of the fossil record to show that such methods are entirely capable of recovering an explosive diversification of angiosperms if the fossil record can be interpreted confidently to support this. We argue that older putative angiosperm records have insufficient claim on crown-angiosperm affinity to justify their use in divergence time estimation and, in their absence, estimate crown-angiosperms to have diverged in a Late Jurassic–Early Cretaceous interval. This diminishes the Jurassic gap between molecular clock estimates and literal interpretations of the fossil record but expands the Jurassic gap in the fossil record of stem-angiosperms that is not readily rationalized. Attention should be refocused on the history of stem-angiosperms in which the body plan of this most successful lineage of land plants was assembled.